Role of the neuropeptide CCAP in Drosophila cardiac function. - Dulcis, D.; Levine, R.B.; Ewer, J. (Journal of Neurobiology, 2005)
The heartbeat of adult Drosophila melanogaster displays two cardiac phases, the anterograde and retrograde beat, which occur in cyclic alternation. Previous work demonstrated that the abdominal heart becomes segmentally innervated during metamorphosis by peripheral neurons that express crustacean cardioactive peptide (CCAP). CCAP has a cardioacceleratory effect when it is applied in vitro. The role of CCAP in adult cardiac function was studied in intact adult flies using targeted cell ablation and RNA interference (RNAi). Optical detection of heart activity showed that targeted ablation of CCAP neurons selectively altered the anterograde beat, without apparently altering the cyclic cardiac reversal. Normal development of the abdominal heart and of the remainder of cardiac innervation in flies lacking CCAP neurons was confirmed by immunocytochemistry. Thus, in addition to its important role in ecdysis behavior (the behavior used by insects to shed the remains of the old cuticle at the end of the molt), CCAP may control the level of activity of the anterograde cardiac pacemaker in the adult fly. Expression of double stranded CCAP RNA in the CCAP neurons (targeted CCAP RNAi) caused a significant reduction in CCAP expression. However, this reduction was not sufficient to compromise CCAP's function in ecdysis behavior and heartbeat regulation.